2023
DOI: 10.1097/ms9.0000000000001259
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical characteristics, diagnosis, and complications of scrub typhus infection in Nepal: a systematic review

Pratik Lamichhane,
Kailash M. Pokhrel,
Baraa Alghalyini
et al.

Abstract: Introduction: Scrub typhus (ST) is a neglected tropical disease of serious concern in Nepal. This systematic review aims to describe the burden of disease, clinical presentation, and complications of ST infection in Nepal. Methods: A systematic search of PubMed, EMBASE, Google Scholar, and national databases was conducted for any literature published in English between January 2000 and January 2023. Any type of study design (observational studies, case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…The present study revealed fever, myalgia, and headache as the predominant symptoms in Scrub typhus-positive patients. The Lamichhane P et al [22] study shows fever, headache, cough, shortness of breath, nausea, and abdominal pain were the clinical characteristics in decreasing order of occurrence.…”
Section: Discussionmentioning
confidence: 95%
“…The present study revealed fever, myalgia, and headache as the predominant symptoms in Scrub typhus-positive patients. The Lamichhane P et al [22] study shows fever, headache, cough, shortness of breath, nausea, and abdominal pain were the clinical characteristics in decreasing order of occurrence.…”
Section: Discussionmentioning
confidence: 95%
“…The ST incidence follows a seasonal pattern that shows a spike in May, a peak in October, and a decline in November; in both the 1980-1989 and the 2006-2016 periods, 94% of cases occurred during this time [ 35 ]. Lamichhane et al reported a high seroprevalence of scrub typhus among AUFI patients in Nepal, with a case fatality rate of 2.56% [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…The seroprevalence of scrub typhus among the AUFI cases in Nepal was 19.31%. The seroprevalence of scrub typhus among AUFI cases ranged from 5.37% to 40.32% in Nepal [ 36 ]. Alam et al examined cases in the UK, focusing on clinical features of scrub typhus-associated encephalitis syndromes [ 38 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The population is universally susceptible to orientia tsutsugamushi [2], and the incubation period for this disease ranges from 1 to 3 weeks. The disease is characterized by eschar formation, along with other clinical manifestations including fever, headache, cough, shortness of breath, myalgia, nausea, abdominal pain, enlarged lymph nodes, and a skin rash [3]. The severity of the disease can vary from mild fever to multisystem involvement.…”
Section: Introductionmentioning
confidence: 99%